Piecewise affine approximations for quality modeling and control of perishable foods. (7th December 2017) - Xin, Jianbin; Negenborn, Rudy R.; Lin, Xiao
Summary: This paper proposes a new methodology for modeling and controlling quality degradation of perishable foods when zero‐order kinetics are considered. This methodology approximates the nonlinear model of the zero‐order quality kinetics using the piecewise affine (PWA) modeling representation. For obtaining a proper PWA model, two state‐of‐the‐art methods are discussed, and eventually, a hybrid identification‐based PWA model is considered after the comparison. This PWA model is then transformed into a computational mixed logical dynamical model, based on which an optimal control strategy is proposed that balances food quality and associated energy consumption. Furthermore, a model predictive control is proposed for improving energy efficiency when a dynamical weather environment is considered. Simulation experiments illustrate the potentials of the proposed optimal controller and the model predictive controller in a case study involving the bighead carp.